Nitric oxide synthase and its function in animal reproduction: an update - Zhang, Wei; Chen, Su juan; Guo, Li ya; Zhang, Zijing; Zhang, Jia bin; Wang, Xiao meng; Meng, Xiang bo; Zhang, Min ying; Zhang, Ke ke; Chen, Lin lin; Li, Yi wei; Wen, Yuliang; et al. (Frontiers in Physiology, 2023)
Nitric oxide (NO), a free radical labile gas, is involved in the regulation of various biological functions and physiological processes during animal reproduction. Recently, increasing evidence suggests that the biological role and chemical fate of NO is dependent on dynamic regulation of its biosynthetic enzyme, three distinct nitric oxide synthase (NOS) according to their structure, location and function. The impact of NOS isoforms on reproductive functions need to be timely elucidated.Here, we focus on and the basic background and latest studies on the development, structure, importance inhibitor, location pattern, complex functions. Moreover, we summarize the exactly mechanisms which involved some cell signal pathways in the regulation of NOS with cellular and molecular level in the animal reproduction. Therefore, this growing research area provides the new insight into the important role of NOS male and female reproduction system. It also provides the treatment evidence on targeting NOS of reproductive regulation and diseases.